Increased Coral Larval Supply Enhances Recruitment for Coral and Fish Habitat Restoration - Harrison, Peter L.; dela Cruz, Dexter W.; Cameron, Kerry A.; Cabaitan, Patrick C. (Frontiers in Marine Science, 2021)
Loss of foundation reef-corals is eroding the viability of reef communities and ecosystem function in many regions globally. Coral populations are naturally resilient but when breeding corals decline, larval supply becomes limiting and natural recruitment is insufficient for maintaining or restoring depleted populations. Passive management approaches are important but in some regions they are proving inadequate for protecting reefs, therefore active additional intervention and effective coral restoration techniques are needed. Coral spawning events produce trillions of embryos that can be used for mass larval rearing and settlement on degraded but recoverable reef areas. We supplied 4.6 million Acropora tenuis larvae contained in fine mesh enclosures in situ on three degraded reef plots in the northwestern Philippines during a five day settlement period to initiate restoration. Initial mean larval settlement was very high (210.2 ± 86.4 spat per tile) on natural coral skeleton settlement tiles in the larval-enhanced plots, whereas no larvae settled on tiles in control plots. High mortality occurred during early post-settlement life stages as expected, however, juvenile coral survivorship stabilised once colonies had grown into visible-sized recruits on the reef by 10 months. Most recruits survived and grew rapidly, resulting in significantly increased rates of coral recruitment and density in larval-enhanced plots. After two years growth, mean colony size reached 11.1 ± 0.61 cm mean diameter, and colonies larger than 13 cm mean diameter were gravid and spawned, the fastest growth to reproductive size recorded for broadcast spawning corals. After three years, mean colony size reached 17 ± 1.7 cm mean diameter, with a mean density of 5.7 ± 1.25 colonies per m–2, and most colonies were sexually reproductive. Coral cover increased significantly in larval plots compared with control plots, primarily from A. tenuis recruitment and growth. Total production cost for each of the 220 colonies within the restored breeding population after three years was United States $17.80 per colony. A small but significant increase in fish abundance occurred in larval plots in 2018, with higher abundance of pomacentrids and corallivore chaetodontids coinciding with growth of A. tenuis colonies. In addition, innovative techniques for capturing coral spawn slicks and larval culture in pools in situ were successfully developed that can be scaled-up for mass production of larvae on reefs in future. These results confirm that enhancing larval supply significantly increases settlement and coral recruitment on reefs, enabling rapid re-establishment of breeding coral populations and enhancing fish abundance, even on degraded reef areas.